Buprenorphine Supply, Access, and Quality: Where We Have Come and the Path Forward. Issue 2 (June 2018) - Breen, Christopher T.; Fiellin, David A.
Buprenorphine is a form of opioid agonist treatment that has been demonstrated to be an effective medication for opioid addiction. It is available in different formulations and marketed under various trade names, including commonly as a buprenorphine/naloxone combination. This paper provides an overview of existing literature on the supply of buprenorphine treatment, the ability of people to access treatment with buprenorphine, and the quality of treatment received. We argue that better data for each of these aspects of treatment could inform policy to expand effective treatment with buprenorphine, and we suggest steps to obtain and act on such data.